Genome-wide survey and characterization of microsatellites in cashew and design of a web-based microsatellite database: CMDB - Savadi, Siddanna; Muralidhara, B. M.; Venkataravanappa, V.; Adiga, J. D. (Frontiers in Plant Science, 2023)
The cashew is an edible tree nut crop having a wide range of food and industrial applications. Despite great economic importance, the genome-wide characterization of microsatellites [simple sequence repeats (SSRs)] in cashew is lacking. In this study, we carried out the first comprehensive genomewide microsatellites / SSRs characterization in cashew and developed polymorphic markers and a webbased microsatellite database. A total of 54526 SSRs were discovered in the cashew genome, with a mean frequency of 153 SSRs/Mb. Among the mined genome-wide SSRs (2-6 bp size motifs), the dinucleotide repeat motifs were dominant (68.98%) followed by the trinucleotides (24.56%). The Class I type of SSRs (≥20 bp) were 45.10%, while Class II repeat motifs (≥12-<20 bp) were 54.89% of the total genomic SSRs discovered here. Further, the AT-rich SSRs occurred more frequently in the cashew genome (84%) compared to the GC-rich SSRs. The validation of the in silico-mined genome-wide SSRs by PCR screening in cashew genotypes resulted in the development of 59 polymorphic SSR markers, and the polymorphism information content (PIC) of the polymorphic SSR markers ranged from 0.19 to 0.84. Further, a web-based database, "Cashew Microsatellite Database (CMDB)," was constructed to provide access to the genome-wide SSRs mined in this study as well as transcriptomebased SSRs from our previous study to the research community through a user-friendly searchable interface. Besides, CMDB provides information on experimentally validated SSRs. CMDB permits the retrieval of SSR markers information with the customized search options. Altogether, the genome-wide SSRs characterization, the polymorphic markers and CMDB database developed in this study would serve as valuable marker resources for DNA fingerprinting, germplasm characterization, genetic studies, and molecular breeding in cashew and related Anacardium species.